STRONG PRESSING OF LIGHTWEIGHT CONCRETE FROM MIXED STAYROFOAM AS A REPLACEMENT OF A RUDE AGGREGATE - Wahyu Hutria,Nurhasan Syah,Ardiyan (International Conference on Industrial Revolution for Polytechnic Education, 2021)
In line with the economical development, there are a lot of old buildings renovation which produces material waste like stayrofoam. To use the existing stayrofoam waste, the research on the use of stayrofoam waste for concrete mixture was performed considering that stayrofoam is hard enough. By using part of stayrofoam fraction in the aggregate for concrete mixture, it is expected that it doesn’t affect the quality or pressure strength of the produced concrete. This is more economical since the pebble price is more expensive than stayrofoam price. The aim of the research is to find out the percentage of stayrofoam in the coarse aggregate for concrete mixture so that it doesn’t affect the concrete pressure strength, seek for the correlation between concrete pressure strength and the percentage of stayrofoam in coarse aggregate for concrete mixture, seek for the correlation between concrete pressure strength and aggregate weathering. In this research, the testing material is in the form of cube 10 x 10 x 10 cm with 8 test specimens, percentage of stayrofoam tile in the mixture, that is 0, 5, 10, 15 % of its coarse aggregats. From the research results, the compressive strength without stayrofoam 128 kgf / cm2 medium if the aggregate coarsely mixed stayrofoam 5% compressive strength of concrete to 103 kgf / cm2. can be said concrete compressive strength decreased by 24,30 kgf / cm2 at 7 days concrete age. Strong strength without stayrofoam 128 kgf / cm2 moderate when aggregate coarsely mixed stayrofoam 10% concrete compressive strength to 77.90 kgf / cm2. The compressive strength of concrete drops by 50.10 kgf / cm2. However, at stayrofoam mixture 15% compressive strength of concrete at 7 days old was 119,50 kgf / cm2 and decrease only 8,50 kgf / cm2. The addition of stayrofoam affects the compressive strength of the concrete.